Actividades desarrolladas durante el año 2015 en el laboratorio Hypatia s.a” - Delgado Fernández, Jimmy Jack (2016)
This report describes pre professional practices activities in the area of Quality Control of Pharmaceutical Products; which involves making measurements of product parameters, determining whether the values are consistent with predefined specifications. The Quality Control Laboratory Hypatia, meets one of the most important roles in the control of pharmaceutical products, mainly physical and chemical analysis; to define what tests to perform to determine the quality of a given product should resort to Pharmacopeia. Hence the characteristics that must have a product and tests to establish that it meets the minimum quality requirements by the Health Authority are set are defined. It was concluded that the pre professional practices, can implement the knowledge acquired in college and get more experience, through proper identification of relevant tests for each pharmaceutical product and recognizing the appropriate technical standard for each product analyzed